Magnetic sensing at zero field with a single nitrogen-vacancy center. (15th June 2021) - Lenz, Till; Wickenbrock, Arne; Jelezko, Fedor; Balasubramanian, Gopalakrishnan; Budker, Dmitry
Abstract: Single nitrogen-vacancy (NV) centers are widely used as nanoscale sensors for magnetic and electric fields, strain and temperature. Nanoscale magnetometry using NV centers allows for example to quantitatively measure local magnetic fields produced by vortices in superconductors, topological spin textures such as skyrmions, as well as to detect nuclear magnetic resonance signals. However, one drawback when used as magnetic field sensor has been that an external bias field is required to perform magnetometry with NV centers. In this work we demonstrate a technique which allows access to a regime where no external bias field is needed. This enables new applications in which this bias field might disturb the system under investigation. Furthermore, we show that our technique is sensitive enough to detect spins outside of the diamond which enables nanoscale zero-to ultralow-field nuclear magnetic resonance.